Exploring the analytical consequences of ecological subjects unwittingly neglected by the mainstream of evolutionary thought - Rodríguez, Ricardo A.; Duncan, Janelle M.; Vanni, Michael J.; Melkikh, Alexey V.; Delgado, Juan D.; Riera, Rodrigo; Herrera, Ada M.; Camarena, Tomás; Quirós, Ángel; Fernández-Palacios, José M.; Miranda, Jezahel V.; Perdomo, María E.; et al. (Ecological modelling, 2017)
•Ecological uncertainty (QEU) and evolutionary capacitance (EC) are recent findings•QEU & EC vs. gradualism (EG) and the criterion of evolutionary success (CCES).•EG & CCES seem unsustainable from the point of view of ecosystem ecology and physics.•Exploration of consequences, alternative interpretations and roots of this problem.•An interdisciplinary readjustment of our current view about evolution is suitable. The Darwinian interpretation (Di) of evolutionary process, and its subsequent development in the form of modern evolutionary synthesis (MES), plays a paradigmatic role in the mainstream biological thought. However, the main role in the improvement from Di to MES has depended on population genetics. Conventional ecosystem ecology has added relatively few specific insights to this endeavor in spite of the well-known combined selective influence from environment. This article integrates i) recent findings in genetics (i.e.: evolutionary capacitance); ii) orthodox topics as well as recent results from a large set of models in ecosystem ecology which have recently been encompassed under the term “organic biophysics of ecosystem”; and iii) an epistemological analysis of the origin of On the Origin of Species… by reaching four main particular conclusions: (a) Despite the contemporary recognition that any kind of interspecific relationship has an evolutionary influence, the analytical emphasis of Di and MES on competition has been unwittingly oversized because of the paradoxical manner in which mutualism can emerge as an essential evolutionary force starting from competition, being this an unpublished topic that is analyzed in this manuscript by the first time. This link between two interspecific relationships that seem opposite to each other at the first glance is based on quantum effects that are totally unknown in conventional evolutionary theory due to its bias in favor of genetics, neglecting ecological considerations by contrast. (b) A holistic combination of ecological, genetic and evolutionary insights at the ecosystem level additionally confirms that the analytical role of evolutionary gradualism has also been oversized. (c) The main criterion of evolutionary success conventionally applied by Di and MES should be modified given that: (d) the preferential direction of evolutionary process theoretically proposed by Di and MES does not match with the direction of spontaneous development of natural ecosystems. The final section of this manuscript explains that these four critical outcomes in regard to Di and MES seem to have their root in epistemological inaccuracies involved in the origin of On the Origin of Species…that have been passed from generation to generation without being subjected to interdisciplinary scrutiny. This article showcases the need to review some of the foundational principles of Di and MES before building a “new floor” (i.e.: the extended evolutionary synthesis) supported on our current perspective about the evolutionary process. So, contrastingly with the genocentric nature of conventional evolutionary theory, large sections of our current evolutionary thought could change if we take into account some old results, as well as some recent ones, achieved by means of interdisciplinary approaches. In summary, this article concludes that the MES, despite its correct structure in essential points, could reach a significantly more complete epistemological condition than its current state if we add some fundamental results from ecosystem ecology that have been unwittingly neglected so far.